A simplified, practical, cost-effective surgical approach to sacrospinous colpopexy - Valecha, Shalini Mahana; Dhingra, Divija (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Sacrospinous ligament fixation (SSLF) or colpopexy or colpohysteropexy (when the uterus is conserved) for the treatment of pelvic organ prolapse as a procedure is more than 200 years old. Consequently, umpteen modifications vis-à-vis techniques, instrumentations, lighting options have been described. Most of these make a simple procedure needlessly complex, cumbersome and expensive. We have performed this procedure using a simplified, practical approach with readily available surgical instruments, suture methods and endoscopic lightening apparatus. The main aim of this paper is to highlight the surgical steps of sacrospinous colpopexy performed with simple and easily available routine surgical instruments.